2015
DOI: 10.1016/j.ijantimicag.2015.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Does use of the polyene natamycin as a food preservative jeopardise the clinical efficacy of amphotericin B? A word of concern

Abstract: Natamycin is a poorly soluble, polyene macrolide antifungal agent used in the food industry for the surface treatment of cheese and sausages. This use is not of safety concern. However, highly soluble natamycin-cyclodextrin inclusion complexes have been developed for the protection of beverages. This practice leads to high drug exposures exceeding the safety level. Apart from the definition of an acceptable daily dietary exposure to natamycin, its effect on the faecal flora as a reservoir for resistance has to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 26 publications
0
29
0
1
Order By: Relevance
“…and jeopardizing the clinical efficacy of Amphothericin B [36] has been discussed controversially [37,38]. Evidence has been presented that Natamycin exerts a negligible in vitro resistance-selective potential in pathogenic yeasts and other probably opportunistic fungal pathogens [39].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…and jeopardizing the clinical efficacy of Amphothericin B [36] has been discussed controversially [37,38]. Evidence has been presented that Natamycin exerts a negligible in vitro resistance-selective potential in pathogenic yeasts and other probably opportunistic fungal pathogens [39].…”
Section: Introductionmentioning
confidence: 99%
“…may expose the human faecal Candida spp. flora to antimicrobially active drug concentrations [36]. Consumption of yoghurt containing the novel Natamycin formulation may result in an estimated 2-day daily intake of Natamycin from background and proposed uses for the total US population of 0.61 to 1.22 mg/day [41].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Natamycin or pimaricin is an antibiotic belonging to the group of polyene macrolides produced by actinomycetes Streptomyces natalensis. 2,3 Several studies reported the use of natamycin for the surface treatment of cheeses and dry sausages [4][5][6] and most recently, in antimicrobial packaging systems. 7 Natamycin cannot be added to wines because it is classified as a non-permitted additive by the Code of Enological Practices of the International Organization of Vine and Wine (OIV).…”
Section: Introductionmentioning
confidence: 99%